FEATURES OF THE DEVELOPMENT OF RURAL GREEN TOURISM IN THE KHMELNYT REGION IN THE REALITIES OF THE MARITAL STATE (Development Service Industry Management, 2023)
In the conditions of the unstable situation of the development of the market economy of the Native Krai, the tourism sphere becomes an important and priority socio-economic link. Rural green tourism is one of the modern trends in the field of hospitality. This trend is also confirmed by the fact that rural green tourism is becoming one of the subjects and main priorities of research in this field. It has the potential to change not only the quality of tourism, but also the socio-economic situation of rural areas of Ukraine.The article examines the main component of rural green tourism as an important and priority socio-economic link of Khmelnytskyi region development. The peculiarities of the natural and historical and cultural prerequisites for the development of rural green tourism in Tachinniki, which affect the regional placement of landscape and national-natural parks of Khmelnytskyi region, were clarified. The article substantiates that rural green tourism has the ability to influence the activities of the OTG, in particular, its infrastructure at three levels: territorial, socio-economic and cultural. The peculiarities of the influence of the nature reserve fund of the Khmelnytsky region on the formation of the ecological component of rural green tourism have been clarified. The authors analyze the regularities of the formation of the main centers of development of rural green tourism and the agro-tourism cluster "Oberig", as well as the current state of the tourism enterprise in the countryside in the conditions of a full-scale war. So, in the article, the regularities and main trends of the development of rural green tourism in the Khmelnytskyi region were substantiated.
Keywords: rural green tourism; natural and historical-cultural resources; landscape and national-natural parks; nature reserve fund; entrepreneurship in the field of tourism; agro-tourism cluster